Immunogenicity and safety of the RTS, S/AS01 malaria vaccine co-administered with measles, rubella and yellow fever vaccines in Ghanaian children: A phase IIIb, multi-center, non-inferiority, randomized, open, controlled trial. Issue 18 (16th April 2020) - Asante, Kwaku Poku; Ansong, Daniel; Kaali, Seyram; Adjei, Samuel; Lievens, Marc; Nana Badu, Lydia; Agyapong Darko, Prince; Boakye Yiadom Buabeng, Patrick; Boahen, Owusu; Maria Rettig, Theresa; Agutu, Clara; Benard Ekow Harrison, Samuel; et al.
Highlights: First RTS, S/AS01 dose was given with Vitamin A supplementation at 6 months of age. Third RTS, S/AS01 dose was given with yellow fever and measles-rubella vaccines at 9 months. Immune responses following co-administration met all non-inferiority criteria. The safety profile of the vaccines was clinically acceptable when co-administered. RTS, S/AS01 can be given with Vitamin A, yellow fever and measles-rubella vaccines. Abstract: Background: To optimize vaccine implementation visits for young children, it could be efficient to administer the first RTS, S/AS01 malaria vaccine dose during the Expanded Programme on Immunization (EPI) visit at 6 months of age together with Vitamin A supplementation and the third RTS, S/AS01 dose on the same day as yellow fever (YF), measles and rubella vaccines at 9 months of age. We evaluated the safety and immunogenicity of RTS, S/AS01 when co-administered with YF and combined measles-rubella (MR) vaccines. Methods: In this phase 3b, open-label, controlled study (NCT02699099), 709 Ghanaian children were randomized (1:1:1) to receive RTS, S/AS01 at 6, 7.5 and 9 months of age, and YF and MR vaccines at 9 or 10.5 months of age (RTS, S coad and RTS, S alone groups, respectively). The third group received YF and MR vaccines at 9 months of age and will receive RTS, S/AS01 at 10.5, 11.5 and 12.5 months of age (Control group). All children received Vitamin A at 6 months of age. Non-inferiority of immune responses to the vaccine antigens was evaluated 1 month following co-administration versus RTS, S/AS01 or EPI vaccines (YF and MR vaccines) alone using pre-defined non-inferiority criteria. Safety was assessed until Study month 4.5. Results: Non-inferiority of antibody responses to the anti-circumsporozoite and anti-hepatitis B virus surface antigens when RTS, S/AS01 was co-administered with YF and MR vaccines versus RTS, S/AS01 alone was demonstrated. Non-inferiority of antibody responses to the measles, rubella, and YF antigens when RTS, S/AS01 was co-administered with YF and MR vaccines versus YF and MR vaccines alone was demonstrated. The safety profile of all vaccines was clinically acceptable in all groups. Conclusions: RTS, S/AS01 can be co-administered with Vitamin A at 6 months and with YF and MR vaccines at 9 months of age during EPI visits, without immune response impairment to any vaccine antigen or negative safety effect.